2015
DOI: 10.1371/journal.pgen.1005050
|View full text |Cite
|
Sign up to set email alerts
|

Complex Genomic Rearrangements at the PLP1 Locus Include Triplication and Quadruplication

Abstract: Inverted repeats (IRs) can facilitate structural variation as crucibles of genomic rearrangement. Complex duplication—inverted triplication—duplication (DUP-TRP/INV-DUP) rearrangements that contain breakpoint junctions within IRs have been recently associated with both MECP2 duplication syndrome (MIM#300260) and Pelizaeus-Merzbacher disease (PMD, MIM#312080). We investigated 17 unrelated PMD subjects with copy number gains at the PLP1 locus including triplication and quadruplication of specific genomic interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
121
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(137 citation statements)
references
References 50 publications
6
121
0
Order By: Relevance
“…The nonrecurrent junctions in these patients were consistent with MMBIR [Beck et al, 2015]. This contention is supported by the observation of triplicated and quadruplicated segments, point mutations being associated with some of the breakpoint junctions, and the presence of intrachromosomal rearrangements [Carvalho et al, 2013;Beck et al, 2015].…”
supporting
confidence: 62%
See 2 more Smart Citations
“…The nonrecurrent junctions in these patients were consistent with MMBIR [Beck et al, 2015]. This contention is supported by the observation of triplicated and quadruplicated segments, point mutations being associated with some of the breakpoint junctions, and the presence of intrachromosomal rearrangements [Carvalho et al, 2013;Beck et al, 2015].…”
supporting
confidence: 62%
“…Duplication of the X-linked proteolipid protein 1 (PLP1) gene is the major mutational cause for Pelizaeus-Merzbacher disease and explains ∼ 80% of the cases. This duplication occurs via a mechanism that results in a DUP-TRP/INV-DUP structure [Carvalho et al, 2011;Beck et al, 2015]. An IR distal to PLP1 facilitates DUP-TRP/INV-DUP formation as well as an inversion, a structural variation found frequently among healthy individuals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In patient samples, the PLP1 and MECP2 locus consisted of an inverted triplicated segment flanked by duplicated segments (DUP-TRP/INV-DUP). This kind of rearrangement in both genes was proposed to be facilitated by inverted repeats and was suggested to occur by a two-step process involving BIR followed by MMBIR (Carvalho et al 2013;Beck et al 2015). This hypothesis was recently proved in a pif1Δ yeast strain, where it was demonstrated that the collapse of a replication fork during BIR led to the initiation of MMBIR.…”
Section: Fork Stalling and Template Switching (Fostes)/ Microhomologymentioning
confidence: 95%
“…FoSTeS/MMBIR has also been used to explain the process of chromoanasynthesis, which involves a combination of chromosomal rearrangements with both losses and gains in copy number (Liu et al 2011b;Carvalho et al 2011Carvalho et al , 2013Carvalho et al , 2015Beck et al 2015). This model was proposed to explain the nonrecurrent duplications of the PLP1 gene associated with the demyelinating disorder Pelizaeus-Merzbacher disease (PMD).…”
Section: Fork Stalling and Template Switching (Fostes)/ Microhomologymentioning
confidence: 99%